Analysis of Posidonia oceanica’s Stress Factors in the Marine Environment of Tremiti Islands, Italy - Martina Fattobene; Elisa Santoni; Raffaele Emanuele Russo; Silvia Zamponi; Paolo Conti; Adelmo Sorci; Muhammad Awais; Fuyong Liu; Mario Berrettoni (Molecules, 2024)
Posidonia oceanica significantly contributes to the health of oceans and coastal areas; however, its progressive decline is becoming an increasing source of concern. The present preliminary study aims to assess the chemical parameters that describe the state of preservation of the aforementioned plant meadows located in the Tremiti Islands archipelago. To better understand the plants’ response to external factors, the emission of biogenic volatile organic compounds (BVOCs) was investigated using Posidonia oceanica as a biological indicator. Subsequently, the heavy metal concentrations (Ag, Al, As, Ba, Be, Cd, Co, Cr, Cu, Fe, Mn, Mo, Ni, Pb, Sb, Se, Sn, Ti, Tl, V, Zn) in sediments, leaves, and seawater were determined and pollution indicators were calculated to assess the deviation from the natural background levels of sediments. The dimethyl sulfoniopropionate (DMSP) to dimethyl sulfoxide (DMSO) ratio was calculated to evaluate the oxidative stress levels in the meadows because the DMSP naturally present in Posidonia oceanica is oxidized to DMSO and decreases the ratio of DMSP/DMSO. BVOC analysis revealed dimethyl sulphide (DMS) as the most abundant molecule. Morphological features led to variations in metal concentrations across sampling sites, with sheltered bays displaying a higher metal content. Degradation is indicated by a greater DMSO content in the outer leaves. In accordance with the metal content, the bioindicator ratio confirms greater degradation on the south side, which aligns with increased oxidative stress.